Peran Strategis Kuliah Kerja Nyata Mahasiswa dalam Pencegahan Stunting, Digitalisasi UMKM, dan Pemberdayaan Loseda - Fitrie Altianti; Herni Supartika; Nabil Ahnaf Rustiana; Yuliyantini (LPPM Universitas Langlangbuana, 2025)
The Student Community Service (KKN) program in Babakan Tarogong Village addressed three main issues: stunting prevention, digitalization of micro, small, and medium enterprises (UMKM), and organic waste management through Kitchen Waste Pits (Loseda). The program aimed to raise community awareness on health and nutrition, enhance UMKM digital literacy, and promote environmental sustainability. Methods included health education, door-to-door socialization on QRIS digital payments, and practical demonstrations of Loseda construction and use. Results showed improved parental knowledge on stunting, increased UMKM awareness of digital payment systems, and household-level organic waste management through a maggot house for compost production. The program highlights the importance of an interdisciplinary approach, active community participation, and sustained collaboration among universities, local governments, and residents for sustainable community development.